Hyperventilation-induced changes of blood cell counts depend on hypocapnia - Stäubli, Max; Vogel, F.; Bärtsch, Peter; Flückiger, G.; Ziegler, W. H. (European journal of applied physiology, 1994)
Voluntary hyperventilation for 20 mm causes haemoconcentration and an increase of white blood cell and thrombocyte numbers. In this study, we investigated whether these changes depend on the changes of blood gases or on the muscle work of breathing. A group of 12 healthy medical students breathed 36 l· min−1 of air, or air with 5% CO2 for a period of 20 min. The partial pressure of CO2 decreased by 21.4 mmHg (2.85 kPa;P < 0.001) with air and by 4.1 mmHg (0.55 kPa;P < 0.005) with CO2 enriched air. This was accompanied by haemoconcentration of 8.9% with air (P < 0.01) and of 1.6% with CO2 enriched air (P < 0.05), an increase in the lymphocyte count of 42% with air (P < 0.001) and no change with CO2 enriched air, and an increase of the platelet number of 8.4% with air (P < 0.01) and no change with CO2 enriched air. The number of neutrophil granulocytes did not change during the experiments, but 75 min after deep breathing of air, band-formed neutrophils had increased by 82% (P < 0.025), whereas they were unchanged 75 min after the experiment with CO2 enriched air. Adrenaline and noradrenaline increased by 360% and 151% during the experiment with air, but remained unchanged with CO2 enriched air. It was concluded that the changes in the white blood cell and platelet counts and of the plasma catecholamine concentrations during and after voluntary hyperventilation for 20 min were consequences of marked hypocapnic alkalosis. It was found that minimal changes of the blood gases, the muscle work of breathing, the chest movements or mechanical influences on the spleen did not contribute to hyperventilation-induced changes of these variables.